Influence of ultrasound contrast agents on spectral Doppler analysis in recipients of liver transplantation - Cho, Young Seo (Clin Mol Hepatol, 2017)
BACKGROUND/AIMS: Clinical validation is required to determine whether Doppler measurements are comparable before and after administering ultrasound contrast agent (USCA). The purpose of this study is to explore whether the use of USCA affects spectral Doppler analysis in recipients of liver transplantation (LT). METHODS: For this study, 36 patients were examined using Doppler ultrasonography (US) along with a contrast-enhanced US for surveillance of vascular complications after LT. The following spectral Doppler US parameters were measured before and after administration of USCA: peak systolic velocity, end-diastolic velocity, resistive index, and systolic acceleration time of the graft hepatic artery; peak flow velocity of the graft portal vein; and peak flow velocity and venous pulsatility index of the graft hepatic vein. RESULTS: The mean peak systolic and end-diastolic velocities of the hepatic artery and the peak flow velocity of the portal and hepatic veins were increased after intravenously administration of the USCA, ranging from 10% to 13%. However, the changes were not statistically significant (P=0.097, 0.103, 0.128, and 0.190, respectively). There were no significant differences in other measured parameters, including the resistive index (P=0.205) and systolic acceleration time (P=0.489) of the hepatic artery and venous pulsatility index (P=0.494) of the hepatic vein. CONCLUSIONS: The measured velocities of graft hepatic vessels tended to increase after administration of USCA, but without statistical significance. The comparison of serial Doppler parameters with or without injection of USCA is valid during Doppler surveillance in recipients of LT.